Analisis ALT Dan Kandungan Protein Pada Kerupuk Ikan Gabus (Channa Striata) Di Ud Bunda Foods - Wildan Wahyu Ananta; Senja Ikerismawati (CV. SINAR HOWUHOWU, 2025)
This study aims to analyze the microbiological quality and nutritional content of snakehead fish crackers (Channa striata) produced by UD Bunda Foods. The parameters analyzed include Total Plate Count (TPC) as an indicator of microbiological safety, and protein content as a measure of nutritional value. Laboratory testing was conducted using the Standard Plate Count method (for TPC) and the Kjeldahl method (for protein content), with results compared to the standards set by SNI 8272:2016. The findings showed that the TPC values ranged from 3.7 × 10³ to 3.9 × 10³ CFU/g, which is well below the maximum allowable limit of 1.0 × 10⁴ CFU/g. Protein content ranged from 6.91% to 6.96%, exceeding the minimum requirement of 5%. These results confirm that the fish crackers are microbiologically safe, nutritionally valuable, and comply with national food quality standards. The study highlights the importance of hygienic production practices and the use of high-quality raw materials in ensuring product safety and competitiveness, particularly in the small and medium fish-processing enterprises (SMEs) sector.